2015
DOI: 10.1186/s12906-015-0637-0
|View full text |Cite
|
Sign up to set email alerts
|

Large dose means significant effect – dose and effect relationship of Chi-Dan-Tui-Huang decoction on alpha-naphthylisothiocyanate-induced cholestatic hepatitis in rats

Abstract: BackgroundLarge dose application of traditional Chinese medicines has attracted more and more attentions in recent years. However, the scientific connotation of large dose application has not been clarified so far. The present study was designed to investigate the protective effects of Chi-Dan-Tui-Huang decoction (CDTHD) against Alpha-naphthylisothiocyanate (ANIT) induced acute cholestatic hepatitis in rats and explore the dose-effect relationship of CDTHD as a reference for clinical application.MethodsThe adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
(21 reference statements)
2
12
0
Order By: Relevance
“…In three PLP‐treated groups, different doses (20, 40 and 80 g/kg body weight, respectively) of PLP (dissolved in normal saline) were administered via intragastric gavage for five consecutive days and received 60 mg/kg ANIT on the third day. The doses of PLP used in this research were in line with previous experiments and were proved as no toxic reactions in rats …”
Section: Methodssupporting
confidence: 78%
See 3 more Smart Citations
“…In three PLP‐treated groups, different doses (20, 40 and 80 g/kg body weight, respectively) of PLP (dissolved in normal saline) were administered via intragastric gavage for five consecutive days and received 60 mg/kg ANIT on the third day. The doses of PLP used in this research were in line with previous experiments and were proved as no toxic reactions in rats …”
Section: Methodssupporting
confidence: 78%
“…A genomewide microarray analysis revealed that paeonol shows the anti‐inflammation effects mediated by chemokine and cytokine signalling in LPS‐treated RAW264.7 macrophages . According to our previous study, the aqueous extract of PLP was clinically effective to cholestatic hepatitis and suggested that PLP played its role against cholestasis by its anti‐oxidation and free radical scavenger effect . That study also pointed out that the anticholestasis effect of PLP is closely associated with oxidative stress as well as other influencing factors, such as inflammation and imbalance of bile acid.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…RR as an example, the dosage to treat cholestasis in clinical is more than four times the regular dose recommended in the Chinese pharmacopeia (Zhang et al, 2016). For now, the widespread explanation is that drug should be administrated to the patient with the correct disorder indications, otherwise it will produce dosage variety and individual detrimental effect (Zhao et al, 2015). As displayed in Table 5, dosage of constituents from SHXXT has a big range with no obvious rule to follow, it is possibly due to different tested animals or cells may have different drug sensitivities, but still need further clarification.…”
Section: Discussionmentioning
confidence: 99%